Perception and Conceptualization of the Land-Grant Mission at a Land-Grant Institution - Audrey E. H. King; Quisto Settle; Dwayne Cartmell; Asya Cooley; Jeff Sallee (Journal of Applied Communications, 2022)
While the three-part mission of the land-grant university has been a pivotal component of agriculture and natural resources in the U.S., the land-grant mission is not always well understood by all audiences, including faculty members who are the key deliverers of the land-grant mission. As such, it is important to understand how faculty members view the land-grant brand identity. A series of focus groups were conducted with tenure and non-tenure track faculty members at [university]. Faculty members’ perceptions of the university’s brand came out in four themes: overall description of the brand identity, connections to [City], university values, and increased emphasis on research. How faculty members conceptualized the land-grant mission presented two themes: aware but uninformed about the land-grant mission (subthemes: concerns about public awareness and stakeholder priorities, and unawareness of Extension) and having varying definitions of the land-grant mission (subthemes: land-grant is about the land, the land-grant mission is for more than agriculture, the land-grant is successful when serving the state, the land-grant mission is intended to improve society, and the land-grant mission is delivering equal opportunity education). Recommendations for universities included providing faculty members with a full understanding of the land-grant missions and ensuring students are taught about the land-grant mission. Future research was recommended to assess perceptions of faculty members at other land-grant universities and perceptions of non-faculty audiences such as students and external stakeholders. A quantitative survey was also recommended to provide a more generalizable view of faculty perceptions of the brand of land-grant universities.
Keywords: Land-grant universities; internal branding; faculty members; online focus groups; Extension